A Milton Chronology - Campbell, G. author. aut Link
XII, 255 p.
Keywords: In this chronology Gordon Campbell brings his unique command of manuscripts associated with John Milton to the first synthesis of the Milton documents attempted in forty years. Many manuscripts that have been lost to view have been rediscovered, and some manuscripts that have never been seen by students of Milton are recorded here for the first time. These new discoveries, together with many unrecorded printed allusions that have never been integrated into biographical studies of Milton, make this chronology an essential research and reference tool that creates a new context for many of Milton's poems and prose writings.